Serum 25-hydroxyvitamin D concentration does not correlate with atopic dermatitis severity - Chiu, Yvonne E. (2013)
BACKGROUND: An inverse correlation between serum 25-hydroxyvitamin D concentration and atopic dermatitis (AD) severity has been suggested. OBJECTIVE: To determine if a statistically significant relationship exists between serum 25-hydroxyvitamin D concentration and AD severity. METHODS: A cross-sectional study was conducted of patients with AD aged 1–18 years. An objective Severity Scoring of Atopic Dermatitis (SCORAD) and a serum 25-hydroxyvitamin D concentration were measured for each subject. Statistical analysis was performed using appropriate univariate tests and multivariable models. RESULTS: Ninety-four of 97 enrolled subjects were included in the analysis. Vitamin D deficiency (25-hydroxyvitamin D <20ng/ml) was present in 37 (39%), insufficiency (25-hydroxyvitamin D 21–29 ng/mL) in 33 (35%), and sufficiency (25-hydroxyvitamin D ≥30 ng/ml) in 24 (26%). The correlation between 25-hydroxyvitamin D concentration and SCORAD was not significant (r=−0.001, p=0.99). A multivariate model showed that a lower serum 25-hydroxyvitamin D concentration was significantly associated with age ≥3-years (p<0.0001), black race (p<0.0001), and winter season (p=0.0084). LIMITATIONS: Limitations of this study include the inability to control for natural sunlight exposure, vitamin D intake and AD treatment, and that only a single time point was captured. CONCLUSIONS: Serum 25-hydroxyvitamin D concentration is not significantly correlated with AD severity in our pediatric population.